KEPENTINGAN INDONESIA BERGABUNG KE DALAM BRICS (BRAZIL, RUSSIA, INDIA, CHINA AND SOUTH AFRICA) - Nabila Ultami Putri; Arif Wicaksa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to examine and understand Indonesia’s interests in joining BRICS (BRAZIL, RUSSIA, INDIA, CHINA AND SOUTH AFRICA), as well as how this move relates to efforts to reduce dependence on Western influence, particularly in the economic and financial sectors. The background of this study stems from shifting global conditions that are moving toward a multipolar system, where dominance is no longer limited to Western nations but is increasingly challenged by emerging powers from developing countries. This study employs a qualitative method using a literature review approach. In analyzing the issues, the author utilizes a postcolonial perspective to examine efforts to break free from dependence on the West, as well as interdependence theory to explain the interdependent relationships among nations that are not always balanced. This membership opens opportunities to reduce dependence on the dollar through de-dollarization efforts, expand markets, and secure alternative sources of development financing. Indonesia’s participation in BRICS does not mean turning away from the West, but rather an effort to expand cooperation options and adapt to global changes, in accordance with the principle of an independent and active foreign policy. Keywords: BRICS, Indonesia, dedollarization.